Capital Ideas: The Improbable Origins of Modern Wall Street. - LeRoy, Stephen F.; Bernstein, Peter L. (Journal of Finance, 1992)
Acknowledgments. Introduction: The Revolution in the Wealth of Nations. PART I: SETTING THE SCENE. Chapter 1. Are Stock Prices Predictable? PART II: THE WHOLE AND THE PARTS. Chapter 2. Fourteen Pages to Fame. Chapter 3. The Interior Decorator Fallacy. Chapter 4. The Most Important Single Influence. PART III: THE DEMON OF CHANCE. Chapter 5. Illusions, Molecules, and Trends. Chapter 6. Anticipating Prices Properly. Chapter 7. The Search for High P.Q. PAR IV: WHAT ARE STOCKS WORTH? Chapter 8. The Best at the Price. Chapter 9. The Bombshell Assertions. Chapter 10. Risky Business. Chapter 11. The Universal Financial Device. PART V: FROM GOWN TO TOWN. Chapter 12. The constellation. Chapter 13. The Accountant for Risk. Chapter 14. The Ultimate Invention. PART VI: THE FUTURE. Chapter 15. The View form the Top of the Tower. Notes. Bibliography and Other Sources. Name Index. Subject Index.